2017
DOI: 10.3390/min8010002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometallurgical Processing Technology of Titanomagnetite Ores

Abstract: In this paper, we study the possibility of obtaining iron and titanium-vanadium concentrates with highest contents of iron and titanium, respectively, through hydrometallurgical processing of the titanomagnetite ores of the Chineisk deposit. We varied two key parameters to determine the efficiency of the process: (a) concentration of leaching solution (ammonium fluoride); and (b) acidity of solution. Ammonium fluoride concentration was varied from 0.08 mol/L to 4.2 mol/L with the other fixed parameters. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Fluorination of rutile must be carried out in two stages. At the first stage, according to reactions (2)(3)(4)(5)(6)(7)(8)(9)(10), in an excess of elemental fluorine at 1500-2000 K, the process of fluorination of rutile concentrates proceeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorination of rutile must be carried out in two stages. At the first stage, according to reactions (2)(3)(4)(5)(6)(7)(8)(9)(10), in an excess of elemental fluorine at 1500-2000 K, the process of fluorination of rutile concentrates proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…An aquatic technology is being developed for opening titanomagnetite ore by selective extraction of titanium with solutions containing ammonium fluoride (ammonium and fluorine ions) [9]. A technology based on the use of metal and ammonium hydrofluorides for opening titanium ores and concentrates is presented [10].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the fluoride processing method of ilmenite and rutile is very actively developing [23][24][25][26][27][28]. This method is very promising and has a very strong basis for the development of this technology, because it is economical, has a low amount of waste, and has the ability to recycle the main components [29][30][31][32][33][34][35][36][37]. For example, the authors of [29,30,37] worked with titanium dioxide, which is found in industrial waste or in low-grade materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, it complicates the application of this technology in practice. The studies [33][34][35][36][37] describe the leaching of titanium-bearing raw materials by the hydrometallurgical method using hydrofluoric acid. The optimal parameters were established, which differ due to the use of raw materials with different chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) have become very attractive as relatively novel catalysts in nano‐green technology due to their extraordinary features including, high surface area, high stability, easy functionalization, easy synthesis and simple separation from reaction mixtures using an external magnet, which eliminates the need for tedious isolation processes such as filtration or centrifugation . Titanomagnetite (Fe 3‐x Ti x O 4 ) NPs are among the most important and well‐known species of magnetic nanocatalytic, especially due to the existing of Ti +4 cations in NPs structure that lead to increas the number of surface hydroxyl groups and higher loading capacity of grafted functional groups on the surface of NPs . It should also be kept in mind that, titanomagnetite NPs were first introduced by Azarifar et al.…”
Section: Introductionmentioning
confidence: 99%